Rituximab – A novel therapy for severe ITP in pregnancy: A case report. (December 2019) - Donohoe, Fionan; Higgins, Mary; Higgins, Shane; McAuliffe, Fionnuala; Murphy, Karen
Background: Rituximab is a novel second-line agent for the treatment of immune thrombocytopenic purpura. Minimal data exist on the use of rituximab in pregnancy. This case illustrates the successful treatment of severe immune thrombocytopenic purpura diagnosed in pregnancy, refractory to all other medical management. Case: A 32-year-old nulliparous woman was diagnosed with severe immune thrombocytopenic purpura at the time of booking for antenatal care (platelet level of 13 × 10 9 /L). Standard treatment failed to adequately increase her platelet count. Therapy with rituximab was instituted, and her platelet count rose to normal levels, without side effects, and remained at a normal level throughout the pregnancy. There were no maternal or neonatal ill-effects of rituximab therapy. Conclusion: Rituximab is potentially a safe treatment option for the management of immune thrombocytopenic purpura in pregnancy with good maternal and neonatal outcome when conventional treatments have been unsuccessful. Research is limited to case reports, and therefore limited information currently exists to guide clinicians.